2021
DOI: 10.1097/ajp.0000000000000969
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Serratus Anterior Muscle Plane Block on Persistent Postsurgical Pain After Video-assisted Thoracic Surgery

Abstract: Objectives: Acute pain intensity is a strong indicator for the occurrence of persistent postsurgical pain (PPP) after video-assisted thoracic surgery (VATS). The effect of preoperative serratus anterior muscle plane block (SAPB) on PPP was investigated. Materials and Methods:In this retrospective cohort study, data of 148 patients who underwent VATS for lung nodules in 2019 were collected. Seventy-four patients received a single-shot of SAPB with 0.33% ropivacaine 30 mL after anesthesia induction and another 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Thereafter, 183 records were carefully reviewed to ensure compliance with the inclusion criteria. Ultimately, 17 studies [10][11][12][20][21][22][23][24][25][26][27][28][29][30][31][32][33], comprising 10,525 patients who underwent VATS, were included in this study (Fig. 1).…”
Section: Included Studiesmentioning
confidence: 99%
“…Thereafter, 183 records were carefully reviewed to ensure compliance with the inclusion criteria. Ultimately, 17 studies [10][11][12][20][21][22][23][24][25][26][27][28][29][30][31][32][33], comprising 10,525 patients who underwent VATS, were included in this study (Fig. 1).…”
Section: Included Studiesmentioning
confidence: 99%
“…After removal of 166 records, 56 that met the eligibility criteria were included (Fig. 1) [9, 11, 50–103]. Of the 56 included studies, 28 (50%) were randomised controlled trials, 16 (29%) prospective observational studies and 12 (21%) retrospective observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a number of retrospective studies have investigated the associated risk factors for the development of CPSP after VATS, including body mass index (BMI), history of pain, and acute postoperative pain (13,14,(16)(17)(18)(19). Further, studies have indicated that microRNAs (miRNAs) in the peripheral blood of patients with chronic neuropathic pain are closely associated with chronic neuropathic pain (20-22).…”
Section: Introductionmentioning
confidence: 99%
“…History of chronic pain refers to the baseline level of pain preoperatively, and retrospective studies have demonstrated that preoperative pain increases the risk of the development of CPSP ( 14 ). In addition to preoperative pain, postoperative VAS pain scores on days 1–3 were also positively associated with the occurrence of CPSP after VATS ( 17 ). There have been an increasing number of studies implicating miRNAs in their involvement in the occurrence and maintenance of pain, such as the small molecule miR 550a-3p, although its involvement in CPSP has not been confirmed ( 25 ).…”
Section: Introductionmentioning
confidence: 99%